ANALYSIS OF LIQUID WASTE TREATMENT AT PT PLN (PERSERO) STEAM POWER PLANT (PLTU) UPK NAGAN RAYA - Vivi Ayu Kumalasari; Susy Sriwahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
The Operation of a Steam Power Plant (PLTU) can produce waste, one of which is liquid waste. Liquid waste will be processed at the Wastewater Treatment Plant (WWTP). The data in this study were collected through direct observation and interviews with the environmental department. This research was conducted at PT PLN (Persero) UPK Nagan Raya. The results showed that there were several sources of liquid waste, namely from boiler blowdown, water treatment plant (WTP), chemical cleaning, condenser cooling water, and fuel oil or lubricants. The resulting liquid waste discharge is 3,604 m3/day. At the PLTU PT PLN (Persero) UPK Nagan Raya there is a liquid waste treatment facility called the Wastewater Treatment Plant (WWTP). Chemical and physical processes occur in wastewater treatment at WWTP. There is no waste water quality that exceeds the quality standard limit. As long as the PLTU is still operating, it will produce liquid waste which will be processed at the WWTP.